PENGARUH AZADIRACHTIN A TERHADAP SERANGGA Dolleschalia polibete - KARDfNAN, AGUS; MUSTIKA, IKA; ISKANDAR, MOMO; SUKMANA, CUCU (Pusat Penelitian dan Pengembangan Perkebunan, 1999)
Research on the effect of azadirachtin A isolated from neem tree (Azadirachla tndica A Juss) on msect Dolleschalia polibete. the most potenÂ¬ tial insect destroying Graptophyllum pictum crop was caried out at the Entomological laboratory duing November 1997 to May 1998 The objective of the research was to evaluate the effect of azadirachtin A on some biological aspects of D. polibete. The formulation was obtained from FID Parry Ltd. (India), containing 1% azadirachtin A. The concentration recommended was 2-4 ml of formulation It of water or equal to 20-40 ppm of azadirachtin A The insects tested were obtained by reaing them in a screen house. Research was arranged in a completely randomized design, and randomized block design (for ovicidal). 6 treatments and 4-6 eplications. The treaments were concentrations of azadirachtin A (I) 80 ppm (2) 40 ppm (3) 20 ppm, (4) 10 ppm. (S) 5 ppm and (6) 0 ppm. Research consisted of three activities, i.e. effect of neem extract on (1) insect mortality and the survival rate. (2) as antifeedant, and (3) asovicidaon the insect. Results showed that azadirachtin A killed the insect slowly, it needed 3-10 days. Azadirachtin A acted as a growth inhibitor shown by the fact that at 5 and 10 ppm azadirachtin A, some pupae became malformed adults and other pupae died in a failed molt attempt Azadirachtin functioned as an antifeedant on some adult insects where the pupae were malformed and died on antifeedant and inhibit about 40% of feeding deference. Azadirachtin A also acted as an ovicidal inhibited about 50% egg-hatching.